Gambaran Ketepatan Waktu Penyediaan Rekam Medis Rawat Jalan Di RSUP Fatmawati Tahun 2021 - Arip Budiana; Deasy Rosmala Dewi; Laela Indawati; Lily Widjaja (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
The hospital as a public health service institution is an important part that provides complete individual health services and provides inpatient, outpatient, and emergency services. Provision of medical records is a process of providing medical records starting from searching for medical records to sending medical records to the intended polyclinic for health services in accordance with health service standards. The purpose of this study was to get an overview of the timeliness of providing outpatient medical records at Fatmawati Hospital. In this study the authors decided to use a qualitative descriptive method which aims to describe the situation or field conditions regarding the occurrence of inaccuracies in the provision of outpatient medical records at Fatmawati Hospital. Based on Standard Operating Procedures, the provision of outpatient medical records at Fatmawati Hospital is <30 minutes (maximum 30 minutes), in this study it was found that the timely provision was 75.55%. With an average delivery time of 27,96 minutes. From this it is known that there is a gap related to the time delay in the process of providing medical records. Delays in the process of providing outpatient medical records are caused by factors including factors in the 5M management element which include man, machine, material, money, method. The staff's knowledge factor needs to be improved, the discipline of the supply officer is good but not optimal, the officer has not attended training on the timeliness of providing good medical records. The machine factor is the lack of number of outpatient medical record storage racks, and the lack of a trolley for the provision of medical records. The method factor is the need for periodic socialization of SOPs to remind officers' performance. The matherial factor requires trolly rejuvenation and good maintenance in order to function as it should. The money factor is that the budget should always be a priority that can be a support for the creation of good health services.